2021
DOI: 10.1093/mnras/stab1315
|View full text |Cite
|
Sign up to set email alerts
|

OUP accepted manuscript

Abstract: We present analysis of the galaxy environment and physical properties of a partial Lyman limit system at 𝑧 = 0.83718 with H and metal line components closely separated in redshift space (|Δ𝑣| ≈ 400 km s −1 ) towards the background quasar HE 1003+0149. The 𝐻𝑆𝑇/COS farultraviolet spectrum provides coverage of lines of oxygen ions from O to O . Comparison of observed spectral lines with synthetic profiles generated from Bayesian ionization modeling reveals the presence of two distinct gas phases in the absor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…We analyze the O vi absorption profiles independently and separately from the lower-ionization species, without imposing a common kinematic structure between them. In most cases, the H i column density associated with a more highly ionized gas phase detected in O vi is significantly ( 1 − 2 dex) lower than the N (H i) of the low-ionization phase (e.g., Haislmaier et al 2021;Narayanan et al 2021).…”
Section: Absorption Analysismentioning
confidence: 95%
“…We analyze the O vi absorption profiles independently and separately from the lower-ionization species, without imposing a common kinematic structure between them. In most cases, the H i column density associated with a more highly ionized gas phase detected in O vi is significantly ( 1 − 2 dex) lower than the N (H i) of the low-ionization phase (e.g., Haislmaier et al 2021;Narayanan et al 2021).…”
Section: Absorption Analysismentioning
confidence: 95%
“…Mina et al (2020) demonstrate the impact of feedback from nearby galaxies on halo gas, with larger galaxies suppressing star-formation in their dwarf neighbors. Several recent works have demonstrated that many absorbers likely arise from complex galaxy structures and galaxy groups, not simply single galaxies evolving in isolation (Péroux et al 2019;Hamanowicz et al 2020;Chen et al 2020;Narayanan et al 2021). The high incidence of CGM gas within the virial halos of isolated dwarf galaxies (Johnson et al 2017), coupled with the recent identification of a dwarf galaxy at small projected separation from an absorber initially thought to be associated with a massive galaxy over 300 kpc away (Muzahid et al 2015;Nateghi et al 2021), highlights the need for deep galaxy spectroscopy to fully characterize the galactic environment, critical to understanding the true nature of CGM absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the diffuse gas was likely of tidal origin. Multiple recent searches for galaxies around the sightlines to quasars at the redshifts of intervening absorption by dense HI (Damped Lyman-α systems, MgII absorbers, as well as Lyman limit systems, at redshifts ranging from z = 0.19 to z = 1.5), have found the absorbers to be associated with diffuse gas in between galaxies which are in groups or pairs (Péroux et al 2019;Hamanowicz et al 2020;Dutta et al 2020;Narayanan et al 2021;Weng et al 2021). As for the possibility of presence of molecular gas associated with this excess HI in the intergalactic space, a recent study of CO emission in host galaxies of H 2 absorption selected systems at intermediate redshifts (ranging from z = 0.19 to z = 1.15) interestingly also finds that most of the molecular gas resides in dense gas pockets within the intergalactic medium of groups of galaxies (Klitsch et al 2021).…”
Section: Discussionmentioning
confidence: 99%